Association of Dietary Magnesium Intake with Fatal Coronary Heart Disease and Sudden Cardiac Death - Li, Jason (J Womens Health (Larchmt), 2020)
Background: Postmenopausal women represent the highest population-based burden of cardiovascular disease, including sudden cardiac death (SCD). Our understanding of the etiology and risk factors contributing to fatal coronary heart disease (CHD) and SCD, particularly among women, is limited. This study examines the association between dietary magnesium intake and fatal CHD and SCD. Materials and Methods: We examined 153,569 postmenopausal women who participated in the Women's Health Initiative recruited between 1993 and 1998. Magnesium intake at baseline was assessed using a validated food frequency questionnaire, adjusting for energy via the residual method. Fatal CHD and SCD were identified over an average follow-up of 10.5 years. Results: For every standard deviation increase in magnesium intake, there was statistically significant risk reduction, after adjustment for confounders, of 7% for fatal CHD (hazard ratio [HR] 0.93, 95% confidence interval [CI] 0.89–0.97), and 18% risk reduction for SCD (HR 0.82, 95% CI 0.58–1.15) the latter of which did not reach statistical significance. In age-adjusted quartile analysis, women with the lowest magnesium intake (189 mg/day) had the greatest risk for fatal CHD (HR 1.54, 95% CI 1.40–1.69) and SCD (HR 1.70, 95% CI 0.94–3.07). This association was attenuated in the fully adjusted model, with HRs of 1.19 (95% CI 1.06–1.34) for CHD and 1.24 (95% CI 0.58–2.65) for SCD for the lowest quartile of magnesium intake. Conclusions: This study provides evidence of a potential inverse association between dietary magnesium and fatal CHD and a trend of magnesium with SCD in postmenopausal women. Future studies should confirm this association and consider clinical trials to test whether magnesium supplementation could reduce fatal CHD in high-risk individuals.